The Prevalence and Risk Factors of Gastric Polyp in Asymptomatic Patients Receiving Health Examination - Fu-Wei Wang; Su-Chi Young; Ru-Yih Chen; Kung-Hung Lin; Yan-Hua Chen; Ping-I Hsu; Hsien-Chung Yu (Gastroenterology Research and Practice)
Background. To determine the risk factors and prevalence of asymptomatic gastric polyps in the general population of Taiwan. Methods. Consecutive asymptomatic individuals completing a health examination during October 2015–March 2016 were enrolled in the study and subjected to upper GI endoscopy. Their demographic data and medical history were collected, and the prevalence of gastric polyps was calculated. The risk factors of gastric polyps were identified by analyzing these data through univariate and multivariate logistic regression. Results. Gastric polyp prevalence in the study population was 29.8%. Age range of 45–60 years, current smoking, and lack of regular exercise were found to be significantly associated with gastric polyps, whereas age range of 45–60 years (relative risk [RR], 1.59; 95% confidence interval [CI], 1.06–2.40) and current smoking (RR, 1.63; 95% CI, 1.04–2.55) were found to be independent predictors for gastric polyps. Conclusions. In Taiwan, asymptomatic gastric polyps have a prevalence of 29.8%. Age range of 45–60 years and current smoking may increase the risk of asymptomatic gastric polyps.